Reinforcement Based Concrete Modelling in Commercial Buildings Using Machine Learning Simulations - Sunil Kumar, M.; Kumarasamy, M.; Madhavi, N. Bindu; Dhariwal, Sumit; Sampath Kumar, R.; Oyebode, Oluwadare Joshua (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This study focuses on modelling the strength properties of reinforced concrete containing mineral admixtures using variational auto encoders and artificial neural networks. Knowing that the model projections of force have a low percent error is reassuring information to have. The reliability of the model is further supported by this piece of evidence, which demonstrates that the model is accurate. Due to the significant degree of similarity between the two datasets, this result suggests that the model is credible due to the similarities seen in samples. When all of the criteria are considered, this is a positive indicator that the model that was picked has the potential to effectively forecast the behavior of the system.